PERANCANGAN KEUANGAN SYARIAH PADA IBU RUMAH TANGGA DI DESA SINDANGJAYA - Mumpuni Hayati Nuragustin; Isfandayani Isfandayani; Arief Widyananto; Mas Deden Tirtajaya (Al-Ihsan: Journal of Community Development in Islamic Studies, 2023)
The aimed of this programme is to provide knowledge about Islamic economics and how to manage finances properly. It is also expected to be more aware of the obligation to pay debts, the prohibition of staying away from usury and the importance of saving. With this goal, it is hoped that family life can be happy and far from anxiety. In this programme, socialisation, training and sharing sessions will be conducted. The results of the activity show that the curiosity of mothers in Pulo Rengas, Sindangjaya village is quite high because they still want to learn more about sharia family financial planning. The service method uses community education in the form of socialisation of sharia financial planning. The conclusion of this service is that mothers in Pulo Rengas, Sindangjaya village as the target of the service do not yet have knowledge and understanding of Islamic economics and make sharia financial planning for households which includes three things, namely the obligation to pay debts, avoid the prohibition of usury and the importance of saving.